Pathology and pathogenesis of cutaneous lesions in beef cattle associated with buffalo fly infestation - Naseem, Muhammad Noman; Allavena, Rachel; Raza, Ali; Constantinoiu, Constantin; McGowan, Michael; Turni, Conny; Kamran, Muhammad; Tabor, Ala E.; James, Peter (Frontiers in Veterinary Science, 2023)
Haematobia irritans exigua, commonly known as buffalo fly, is the major hematophagous ectoparasite of north Australian cattle herds. Lesions associated with buffalo fly infestation are generally alopecic, hyperkeratotic, or scab encrusted wounds with variable hemorrhagic ulceration. Buffalo flies can transmit a filarial nematode, Stephanofilaria sp., which has been implicated in the pathogenesis of buffalo fly lesions, but Stephanofilaria infection has not been detected in all lesions suggesting that other causal factors may be involved. This study characterised the pathology of buffalo fly lesions to identify the role of Stephanofilaria in lesion development, as well as to identify other potential agents. Lesion biopsies were collected from north and south Queensland and tested for the presence of Stephanofilaria by qPCR. Each lesion was scored grossly (0-4) for hemorrhage, ulceration, exudation, and alopecia. Lesions were also scored microscopically (0-4) for epidermal and dermal damage and inflammatory characters. Stephanofilaria infection was detected in 31% of lesion biopsies. Grossly, Stephanofilaria-infected lesions had significantly larger lesion area and higher scores for alopecia and hyperkeratosis than lesions where no nematodes were found (P<0.05). Histologically, epidermal, dermal, and adnexal damage was significantly higher in Stephanofilaria infected lesions than lesions without nematodes. Eosinophils, macrophages, and lymphocytes were significantly more abundant in Stephanofilaria positive lesions as compared to negative lesions. This study also noted bacterial infection with colonies of coccoid bacteria, observed in skin sections from 19 lesions. Grossly, lesions with bacterial infection had significantly higher ulceration compared to Stephanofilaria positive lesions, and histologically epidermal disruption was significantly higher in bacteria-infected lesions. We found no evidence of bacteria or Stephanofilaria infection in 49% of the lesions assessed and tissue damage patterns and eosinophilic inflammation suggested hypersensitivity to buffalo fly feeding as a possible cause of these lesions. These findings suggest that although the presence of Stephanofilaria infection may increase the severity of lesion pathology, it is not essential for lesion development. These outcomes also suggest a potential role of bacteria and hypersensitivity in lesion pathogenesis. A better understanding of buffalo fly lesion etiology will contribute to the optimal treatment and control programmes.